Computers & Geosciences - Computers & Geosciences (Elsevier, 2026)
Computers & Geosciences publishes original, high-impact research at the interface between computing/informatics and the geosciences. Submissions must make a substantive contribution in both dimensions: (1) an innovative computational, informatics, or software element, and (2) a clear geoscientific contribution addressing a scientific problem of broad interest to the geoscience community.
FI 0.83
Q1
Keywords: Mathematics & Statistics; Applied Mathematics; Geociencia; Matemáticas aplicadas; Acuerdos transformativos; Transformative agreements; Innovación computacional; Análisis geocientífico; Informática